Impact of artificial feeding policies on space use and competition dynamics in overwintering hooded crane and goose populations - Jong-Ju Son; Ju-Hyun Lee; Jung-Moon Ha; Na-Ru Kang; Sun-Mee Hwang; Jae-Ung Jang; Dae-Han Cho; Se-Yeong Kim; Won-Suk Choi; Yong-Un Shin; Ha-Cheol Sung (PLoS ONE, 2025)
Understanding the spatial distribution of wintering birds in areas with interspecific competition is essential for the development of effective conservation and management strategies. This study investigated habitat use and resource partitioning in hooded cranes ( Grus monacha ) and geese ( Anser albifrons and Anser fabalis ) in Suncheon Bay, UNESCO World Natural Heritage Site. We specifically assessed the impact of habitat management strategies, particularly supplemental feeding, on the species distribution patterns and competition dynamics of hooded cranes and geese. Field surveys conducted from November 2022 to March 2023 revealed that hooded cranes consistently preferred site C-3, a protected area where rice grain is provided through conservation-focused management. In contrast, geese exhibited more adaptable habitat use, shifting their distribution in response to seasonal variations in food availability and the location of the hooded crane population. Utilization rates, electivity indices, and spatial niche analyses indicated that although both species initially overlapped in high-resource areas, geese expanded their spatial niche later in the season, leading to increased spatial separation. The gradual decline in niche overlap suggests resource partitioning as a strategy to reduce interspecific competition. These findings highlight the importance of managing avian conservation programs in a way that takes into account the need to maintaining availability and suitability of habitats for wintering species so as to promote interspecific coexistence amongst migratory bird populations.